2015
DOI: 10.1590/1414-431x20144012
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary exercise prior to traumatic brain injury alters miRNA expression in the injured mouse cerebral cortex

Abstract: MicroRNAs (miRNAs) may be important mediators of the profound molecular and cellular changes that occur after traumatic brain injury (TBI). However, the changes and possible roles of miRNAs induced by voluntary exercise prior to TBI are still not known. In this report, the microarray method was used to demonstrate alterations in miRNA expression levels in the cerebral cortex of TBI mice that were pretrained on a running wheel (RW). Voluntary RW exercise prior to TBI: i) significantly decreased the mortality ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…1). MiR-21 was also shown to be a molecular mediator that improves the cognition in mice subjected to running wheel exercise after TBI (Hu et al, 2015b; Miao et al, 2015). The protective potential of miR-21 might also due to its ability to block apoptosis by acting on the phosphatase and tensin homolog (PTEN)-Akt signaling pathway (Han et al, 2014).…”
Section: Non-coding Rnas and Tbimentioning
confidence: 99%
“…1). MiR-21 was also shown to be a molecular mediator that improves the cognition in mice subjected to running wheel exercise after TBI (Hu et al, 2015b; Miao et al, 2015). The protective potential of miR-21 might also due to its ability to block apoptosis by acting on the phosphatase and tensin homolog (PTEN)-Akt signaling pathway (Han et al, 2014).…”
Section: Non-coding Rnas and Tbimentioning
confidence: 99%
“…MiRNA modulation has been described in TBI; however, their role in pathophysiology of mTBI has not been well studied. MiR-21 has been widely reported to be modulated in the brain tissue following TBI and its upregulation has been shown to be associated with improved neurological outcomes of TBI [21,[38][39][40][41]. In this study, miR-21 was found to be downregulated in the brains of the IS4 group at day 7 postinjury.…”
Section: Discussionmentioning
confidence: 46%
“…We also found that miR-124-3p was downregulated in human perilesional cortex, indicating the translatability of the animal data to the human condition. Recently, Miao and coworkers [21] reported miR-124-3p downregulation in the ipsilateral cerebral cortex in mice exposed to controlled cortical impact-induced TBI. Together, these data suggest that miR-124-3p downregulation is a common post-TBI molecular pathology that does not depend on the model or species investigated.…”
Section: Tbi Causes Downregulation Of Mir-124-3p In the Perilesional mentioning
confidence: 99%
“…TBI regulates brain miRNA expression acutely [14][15][16][17], and some miRNAs remain regulated chronically-months to years after TBI [18,19]. Dysregulated miRNA levels are reported in the cortex [9,14,[20][21][22], hippocampus [15,16,18,19,[23][24][25][26][27], and plasma [28][29][30]. Only a few studies, however, have addressed miRNA expression in patients with TBI [13,19,23,28], highlighting the gap between preclinical and clinical studies.…”
mentioning
confidence: 99%